A survey of the relation between capital structure and corporate strategy - M. La Rocca; T. La Rocca; D. Gerace (Australasian Accounting, Business and Finance Journal, 2008)
This paper responds to the general call for integration between finance and strategy research by examining how financial decisions are related to corporate strategy. In particular, the paper focuses on the link between capital structure and strategy. Corporate strategies complement traditional finance paradigms and extend our insight into a firm’s decisions regarding capital structure. Equity and debt must be considered as financial instruments as well as strategic instruments of corporate governance (Williamson 1988). Debt subordinates governance activities to stricter management, while equity allows for greater flexibility and decisionmaking power. The literature on finance and strategy analyzes how the strategic actions of key players (managers, shareholders, debtholders, competitors, workers, suppliers, etc) affect firm value and the allocation of value between claimholders. Specifically, financing decisions can concern value creation process (1) influencing efficient investments decisions according to the existence of conflict of interest between managers and firm’s financial stakeholders (shareholders and debtholders) and (2) affecting the relationship with non-financial stakeholders, as suppliers, competitors, customers, etc. To summarize, the potential interaction between managers, financial stakeholders, and nonfinancial stakeholders influences capital structure, corporate governance activities, and value creation processes. These in turn, may give rise to inefficient managerial decisions or they may shape the industry’s competitive dynamics to achieve a competitive advantage. A good integration between strategy and finance dimensions can be tantamount to a competitive weapon.
Keywords: Overinvestment; underinvestment; risk-shifting; capital structure; corporate